Challenges in developing a safe nanomedicine based on ocotea duckei vattimo to leishmaniasis treatment: Methodology, nanoparticle development and cytotoxicity assays - Rossetti, Fábia C.; Leal, Sandro S.; Filho, Jose M.B.; Oliveira, Eduardo J.; Barud, Hernane S. [UNESP]; Hori, Juliana I.; Marquele-Oliveira, Franciane; Berretta, Andresa A. (My University, 2014)
Different studies have reported the promising pharmacological activities of yangambin, a lignan from Ocotea duckei Vattimo, mainly as an anti-leishmanial and antitumor compound. However, this lignan has demonstrated to be commonly isolated only as a mixture of diastereoisomers. In this regard, here it is described for the first time, the separation and quantification of yangambin diastereoisomers through HPLC-DAD. Additionally, it was assessed the loading of the Lignan Fraction (LF) from Ocotea duckei, rich in yangambin diastereoisomers, in a nanopharmaceutical formulation followed by the assessment of their effects on macrophage citotoxicity. To this, a RP-HPLC-DAD method was developed and validated; biomarkers identity and purity were assessed by UV profile, IR, ESI-IT MS,13C and1H NMR and melting point range. Lipid nanoparticles were obtained by the microemulsion method. Cytotoxicity studies were conducted in bone marrow-derived macrophages (BMDMs) from C57BL/6 mice by quantification of propidium iodide (PI) uptake. The results showed that this novel, fast and reliable HPLC-DAD methodology allowed the simultaneous separation and quantification of yangambin and its diastereoisomer, epi-yangambin, in Ocotea duckei extract. Lignan Fraction and LF loaded nanoparticles. In addition, the method was validated according to ICH and ANVISA (Brazilian) standards. The LF loaded nanoparticles demonstrated to be in nanometer range and the encapsulation efficiency (EE) was 55.72±1.33% for YAN and 66.11±9.29% for EPI-YAN. The cytotoxicity studies revealed that in the LF fraction (20 and 40μg/mL), neither YAN (3 and 6μg/mL) nor EPI-YAN (3.5 and 7μg/mL) were toxic to macrophages for up to 18 hours of treatment. These results confirmed the low toxicity of Ocotea duckei lignan rich fraction and its isolated compounds, in mammalian macrophages, enabling them to be used in future biological studies. On the other hand, besides LF loaded nanoparticle presented nanoscale profile, it requires adjustments to safely deliver LF to macrophages.
Keywords: Citotoxicity; HPLC; Lignan; Lipid nanoparticle; Method validation; Ocotea duckei; Yangambin